2021
DOI: 10.33448/rsd-v10i14.21549
|View full text |Cite
|
Sign up to set email alerts
|

Wood characterization of Tectona grandis L. F. cultivated in Brazil: a review of the last 30 years

Abstract: Worldwide, Tectona grandis (teak) is recognized for its productivity and the quality of its wood. The Brazilian market is already seen as a great potential for consumption and production of teak wood. Therefore, the objective of this work was to characterize the teak wood grown in Brazil through a bibliographic survey of the results already available. In general, it was found that the teak wood planted in Brazil has a certain variability in its technological properties, and these variations are due to the orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Tropical species such as Anadenanthera peregrina, Ochroma pyramidale, and Schizolobium parahyba Var amazonicum showed the same type of increasing radial variation from pith to bark as J. copaia (Rueda and Williamson, 1992;Valente et al, 2013;Lobão et al, 2012) and the same behavior was found in tropical forest plantation species such as Guazuma crinita, Schizolobium parahyba, Tectona grandis, Toona ciliata, (Chavesta et al, 2020;Lima et al, 2021;Melo et al, 2018;Ribeiro et al, 2011). On the other hand, the tropical species Cariniana legalis also did not present any significant trend of radial variation in the pith-bark direction, the same as the species H. crepitans (Lima et al, 2011;Ribeiro et al, 2011), which does not exist a significant difference in the radial variation of wood in the species H. crepitans is favorable for industrial transformation processes (Plaster et al, 2008;Rios et al, 2018).…”
Section: Discussionmentioning
confidence: 71%
“…Tropical species such as Anadenanthera peregrina, Ochroma pyramidale, and Schizolobium parahyba Var amazonicum showed the same type of increasing radial variation from pith to bark as J. copaia (Rueda and Williamson, 1992;Valente et al, 2013;Lobão et al, 2012) and the same behavior was found in tropical forest plantation species such as Guazuma crinita, Schizolobium parahyba, Tectona grandis, Toona ciliata, (Chavesta et al, 2020;Lima et al, 2021;Melo et al, 2018;Ribeiro et al, 2011). On the other hand, the tropical species Cariniana legalis also did not present any significant trend of radial variation in the pith-bark direction, the same as the species H. crepitans (Lima et al, 2011;Ribeiro et al, 2011), which does not exist a significant difference in the radial variation of wood in the species H. crepitans is favorable for industrial transformation processes (Plaster et al, 2008;Rios et al, 2018).…”
Section: Discussionmentioning
confidence: 71%
“…New studies on wood quality must consider different genetic materials, growing environments, planting spacing, treatments and cutting ages, to allow greater knowledge about growth and factors that can influence the quality of wood produced and the adjustments that can help with forest management, processing and the most appropriate use of wood, in order to consider the best costbenefit ratio (Lima et. al.…”
Section: Introductionmentioning
confidence: 99%
“…A análise de desempenho de qualquer componente estrutural requer o conhecimento das propriedades elásticas do material que o constitui, (Lima, et al, 2021e Santos, et al, 2020. Muitos critérios de resistência que existem apresentam restrições em materiais heterogêneos e anisotrópicos, com propriedades de elasticidade e de resistência direcionais, como a madeira Nicolas et al (2009).…”
Section: Introductionunclassified